2017
DOI: 10.1093/infdis/jix174
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Primary Middle East Respiratory Syndrome Coronavirus Infection in Camel Workers in Qatar During 2013–2014: A Case-Control Study

Abstract: The transmission routes and risk factors for zoonotic Middle East respiratory syndrome coronavirus (MERS-CoV) infections are still unknown. We used the World Health Organization questionnaire for MERS-CoV case-control studies to assess risk factors for human MERS-CoV seropositivity at a farm complex in Qatar. Nine camel workers with MERS-CoV antibodies and 43 workers without antibodies were included. Some camel-related activities may pose a higher risk of MERS-CoV infection, as may cross-border movements of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 14 publications
1
36
1
Order By: Relevance
“…MERS-CoV transmission from camels to human beings is thought to occur via direct contact with camels through respiratory droplets or saliva, or through consumption of camel products, such as milk or undercooked camel meat. 15,18,22,23 Camel to human crossspecies transmission of MERS-CoV has been confirmed by viral RNA sequencing of samples obtained from infected dromedary camels, and from symptomatic 22,23 and asymptomatic patients 24 after known exposure to the infected camels. A study 25 of animal herds associated with patients with MERS-CoV infection in Saudi Arabia found that the nasal swabs of 75 of 584 dromedary camels were positive for MERS-CoV RNA for about 2 weeks, whereas the nasal swabs were negative for MERS-CoV RNA in other animals, including goats, sheep, and cattle.…”
Section: Transmission From Camels To Human Beingsmentioning
confidence: 87%
See 1 more Smart Citation
“…MERS-CoV transmission from camels to human beings is thought to occur via direct contact with camels through respiratory droplets or saliva, or through consumption of camel products, such as milk or undercooked camel meat. 15,18,22,23 Camel to human crossspecies transmission of MERS-CoV has been confirmed by viral RNA sequencing of samples obtained from infected dromedary camels, and from symptomatic 22,23 and asymptomatic patients 24 after known exposure to the infected camels. A study 25 of animal herds associated with patients with MERS-CoV infection in Saudi Arabia found that the nasal swabs of 75 of 584 dromedary camels were positive for MERS-CoV RNA for about 2 weeks, whereas the nasal swabs were negative for MERS-CoV RNA in other animals, including goats, sheep, and cattle.…”
Section: Transmission From Camels To Human Beingsmentioning
confidence: 87%
“…Compared with seroprevalence of MERS-CoV antibody in the general population in Saudi Arabia (0·2%) in 2012-13, seroprevalence was 15 times higher in camel shepherds (two [2·3%] of 87 shepherds had MERS-CoV antibodies; p=0·0004), and 23 times higher in slaughterhouse workers (five of 140 shepherds had MERS-CoV antibodies [3·6%]; p<0·0001). 21 Substantial risk factors were identified for primary MERS-CoV infection among camel workers in Qatar: 18 involvement in animal training, milking camels, workers with respiratory symptoms requiring overnight stay in hospital, contact with camels' waste, and poor hand hygiene before and after animal tasks.…”
Section: Some Risk Factors For Primary and Household Transmission Of mentioning
confidence: 99%
“…Risk factors for MERS-CoV infection among camel workers include milking camels, contact with camel waste, poor hand hygiene before and after animal tasks and training activities, and workers with respiratory symptoms requiring overnight stay in hospital. 21 Viral RNA sequencing has confirmed camel to human transmission of MERS-CoV [22][23][24] after known exposure to the infected camels. Recent data suggest that although MERS-CoV is widespread among dromedary camels in the Middle East and Africa, zoonotic transmission of MERS-CoV from camels to humans is relatively uncommon, and human disease is not directly proportional to potential exposure.…”
Section: Risk Factors For Primary Middle East Respiratory Syndrome Comentioning
confidence: 99%
“…39 Training and milking of camels have been associated with MERS-CoV infection. 42 Consumption of raw camel milk or improperly cooked meat has illustrated high risk of MERS-CoV infection. 1 The emergence of intensive camel livestock system and large trade between countries, particularly from Somalia to Gulf regions, leading to roughly 77,000 live camels being exported each year, can significantly contribute to multiple disease transmissions.…”
Section: Sources and Transmissionmentioning
confidence: 99%